Race and sex differences in erythrocyte Na+, K+, and Na+-K+-adenosine triphosphatase. - Lasker, N (1985)
Several reports indicate that erythrocytes (RBCs) from blacks and men have higher sodium concentrations than those from whites and women. One possible mechanism to explain this finding is a difference in the activity of Na+-K+-ATPase. To explore this possibility, we have studied the Na+ and K+ kinetics of RBC Na+-K+-ATPase and RBC Na+ and K+ concentrations in 37 normotensive blacks and whites, both males and females. The maximal initial reaction velocity (Vmax) values for RBC Na+-K+-ATPase were lower in blacks and men as compared with whites and women. Higher RBC Na+ levels were observed in blacks and males vs. whites and females. Significant inverse correlations were noted between the Na+-K+-ATPase activity and RBC Na+ concentrations. These findings indicate that cellular Na+ homeostasis is different in blacks and men as compared with whites and women. Since higher RBC Na+ concentrations have also been observed in patients with essential hypertension as compared with normotensive subjects, the higher intracellular Na+ concentrations in blacks and men may contribute to the greater predisposition of these groups to essential hypertension.